2009
DOI: 10.1073/pnas.0904514106
|View full text |Cite|
|
Sign up to set email alerts
|

Sustained transgene expression despite T lymphocyte responses in a clinical trial of rAAV1-AAT gene therapy

Abstract: Fig. 2.Transformants releasing E␤C suffered less damage than control lines when EPNs were present. (A) Root damage measured on plants that had received neither WCR eggs nor nematodes was minimal, and there was no difference between transformed and nontransformed plants (n ϭ 5, P ϭ 0.87). (B) Root damage on plants that received only WCR eggs, but no nematodes, was substantial. Again, no significant difference was found between the transformed and nontransformed plants (n ϭ 5, P ϭ 0.18). (C) In plots that receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
243
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 291 publications
(259 citation statements)
references
References 31 publications
14
243
2
Order By: Relevance
“…They observed the presence of the rAAV2 vector up to 20 weeks in human PBMCs, up to 14 weeks in serum and up to 4 weeks in urine, with their highest dose (2E12 vg kg À1 ), which is 8-80-fold higher than the doses administrated to the NHPs in this report. Brantly et al 38 detected rAAV1 vector sequences in human blood up to 90 days after IM injection with the highest dose (1E12vg kg À1 ). These groups used PCR assays with a sensitivity of 50-100 copies in the presence of 1 mg of gDNA.…”
Section: E+07mentioning
confidence: 99%
“…They observed the presence of the rAAV2 vector up to 20 weeks in human PBMCs, up to 14 weeks in serum and up to 4 weeks in urine, with their highest dose (2E12 vg kg À1 ), which is 8-80-fold higher than the doses administrated to the NHPs in this report. Brantly et al 38 detected rAAV1 vector sequences in human blood up to 90 days after IM injection with the highest dose (1E12vg kg À1 ). These groups used PCR assays with a sensitivity of 50-100 copies in the presence of 1 mg of gDNA.…”
Section: E+07mentioning
confidence: 99%
“…T he use of recombinant adeno-associated viral (rAAV) vectors for clinical gene therapy applications has become widespread and is largely due to the demonstration of longterm transgene expression from rAAV vectors in animal models with little associated toxicity and good overall safety profiles in both preclinical and clinical trials Moss et al, 2004;Warrington and Herzog, 2006;Maguire et al, 2008;Mueller and Flotte, 2008;Brantly et al, 2009). Most early AAV gene therapy studies were performed with serotype 2 vectors, but vector systems based on other AAV serotypes with more efficient gene delivery and different tissue specificity are currently in human trials and their use will likely increase (Brantly et al, 2009;Neinhuis, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Most early AAV gene therapy studies were performed with serotype 2 vectors, but vector systems based on other AAV serotypes with more efficient gene delivery and different tissue specificity are currently in human trials and their use will likely increase (Brantly et al, 2009;Neinhuis, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…19,24 For this phase 1 trial, the same hAAT gene cassette used in the first trial was packaged in the AAV1 capsid and 9 AATdeficient (<11 lM) patients were dosed by intramuscular injection. Vector doses were similar to the first trial at 6.9 · 10 12 , 2.2 · 10 13 , and 6.0 · 10 13 vg per subject.…”
Section: Phase 1 Clinical Trial: Aav1 (Published 2009)mentioning
confidence: 99%
“…25 The previous two clinical trials of AAV encoding hAAT used a plasmid transfection method to produce the clinical vector. 19,24 However, previous work has shown that the use of a recombinant herpes simplex virus (HSV) complementation system for rAAV vector production can result in greater vector yields (and modestly increased infectivity of vector on a per vg basis), allowing for dose escalation. 26,27 The HSV complementation system for vector production was validated in a mouse toxicology study comparing it to the previously used traditional transfection method and found that the HSV vector system had increase packaging efficiency as well as increased in vivo vector expression and a similar safety profile as traditionally produced vector.…”
Section: Phase 1 Clinical Trial: Aav1 (Published 2009)mentioning
confidence: 99%